STUDY ON DYNAMIC STABILITY AND BIFURCATION OF THE ROD-FASTENING ROTOR SYSTEM - HEI Di; ZHENG MeiRu (Jixie qiangdu)
The contact effect of the disks of the rod-fastening rotor is considered in this paper. The contact effect is equivalent to a bending resistance spring with nonlinear stiffness when the modal of rod-fastening rotor is established. The motion equation of the rod-fastening rotor system is derived. In order to solve the dynamics responses of the rod-fastening rotor,an effective calculation method is presented by combining the Wilson-θ method and Estimation-correction mechanism. At the same time,Floquet theory is adopted to analyze the bifurcation behaviors of the rod-fastening rotor. The comparison of the stability is implemented between the rod-fastening rotor and integral rotor. The results show that the rod-fastening rotor is more stable than the integral rotor. Finally,the dynamics behaviors of the rod-fastening rotor are analyzed by taking the speed of rotor,eccentricity of disk and stiffness of shaft as control parameter. The calculating results reveal periodic,quasi-periodic,3-periodic,5-periodic of the system.